Aspergillus niger as a Biological Input for Improving Vegetable Seedling Production - Gustavo de Souza Marques Mundim; Gabriel Mascarenhas Maciel; Gilberto de Oliveira Mendes (Microorganisms, 2022)
This study evaluated the potential of Aspergillus niger as an inoculant for growth promotion of vegetable seedlings. Seven vegetable species were evaluated in independent experiments carried out in 22 + 1 factorial schemes, with two doses of conidia (102 and 106 per plant) applied in two inoculation methods (seed treatment and in-furrow granular application), plus an uninoculated control. Experiments were carried out in a greenhouse. Growth parameters evaluated were shoot length, stem diameter, root volume, total root length, shoot and root fresh mass, shoot and root dry mass, and total dry mass. Regardless of the dose and inoculation method, seedlings inoculated with A. niger showed higher growth than uninoculated ones for all crops. The highest relative increase promoted by the fungus was observed for aboveground parts, increasing the production of shoot fresh mass of lettuce (61%), kale (40%), scarlet eggplant (101%), watermelon (38%), melon (16%), pepper (92%), and tomato (42%). Aspergillus niger inoculation also increased seedling root growth of lettuce, pepper, scarlet eggplant, watermelon, and tomato. This research shows that A. niger boosts the growth of all analyzed vegetables, appearing as a promising bio-input for vegetable seedling production.